2010
DOI: 10.1104/pp.110.162487
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That High Activity of Vacuolar Invertase Is Required for Cotton Fiber and Arabidopsis Root Elongation through Osmotic Dependent and Independent Pathways, Respectively      

Abstract: Vacuolar invertase (VIN) has long been considered as a major player in cell expansion. However, direct evidence for this view is lacking due, in part, to the complexity of multicellular plant tissues. Here, we used cotton (Gossypium spp.) fibers, fast-growing single-celled seed trichomes, to address this issue. VIN activity in elongating fibers was approximately 4-6-fold higher than that in leaves, stems, and roots. It was undetectable in fiberless cotton seed epidermis but became evident in initiating fibers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
146
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(156 citation statements)
references
References 47 publications
7
146
0
3
Order By: Relevance
“…Cells in the elongation zone do not divide but expand with endoreduplication, which refers to multiple DNA replication without chromosome segregation . The cell expansion in the elongation zone mainly depends on the relaxation of the cell wall matrix and the expansion of vacuoles (Wang et al 2010). Plant cell expansion largely depends on vacuole development.…”
mentioning
confidence: 99%
“…Cells in the elongation zone do not divide but expand with endoreduplication, which refers to multiple DNA replication without chromosome segregation . The cell expansion in the elongation zone mainly depends on the relaxation of the cell wall matrix and the expansion of vacuoles (Wang et al 2010). Plant cell expansion largely depends on vacuole development.…”
mentioning
confidence: 99%
“…13 In elongating fibers, of sucrose. 12 While collective expression level of GhSus gene members appears to be strong throughout the fiber elongation period 15 ( Fig. 1), GhVIN1, a major vacuolar invertase in cotton fiber, shows evidently higher expression level early in fiber elongation (0-10 DAA) matching high VIN activity observed in this stage.…”
Section: Multiple Players In Controlling Of Cell Turgor During Fiber mentioning
confidence: 99%
“…1), GhVIN1, a major vacuolar invertase in cotton fiber, shows evidently higher expression level early in fiber elongation (0-10 DAA) matching high VIN activity observed in this stage. 12 Transgenic analyses revealed that suppression of GhSus expression reduced fiber length and cellulose content 10 and silencing GhVIN1 decreases fiber elongation. 12 These findings indicate that (1) GhSus play roles in both fiber elongation and cellulose biosynthesis through osmotic regulation and supplying UDPglucose as substrate for cellulose production and hexoses for generation of ATP as an energy source for a variety of transport and metabolic processes (2) GhVIN1 appears to be more specifically required for the formation and enlargement of the central vacuole, pivotal for early fiber elongation (see below).…”
Section: Multiple Players In Controlling Of Cell Turgor During Fiber mentioning
confidence: 99%
See 2 more Smart Citations